2002
DOI: 10.1074/jbc.m207095200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Induction of Mitogen-activated Protein Kinase Phosphatase 1 by Retinoids

Abstract: All-trans-retinoic acid (t-RA) inhibits hydrogen peroxide (H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…We also demonstrated that ERR␣ directly regulates expression of the Dusp1 gene 5= flanking region, which contains an ERR␣-responsive site and is occupied by ERR␣ in a differentiationdependent manner. This is consistent with results from previous studies demonstrating that Dusp1 is regulated by other nuclear receptors, including glucocorticoid and retinoic acid receptors (24,71). Furthermore, a subsequent search using the Ensembl mouse regulatory build (version 4) revealed ERR␤ binding to the proximal Dusp1 promoter in embryonic stem cells within the same region we identified (8,19).…”
Section: Discussionsupporting
confidence: 80%
“…We also demonstrated that ERR␣ directly regulates expression of the Dusp1 gene 5= flanking region, which contains an ERR␣-responsive site and is occupied by ERR␣ in a differentiationdependent manner. This is consistent with results from previous studies demonstrating that Dusp1 is regulated by other nuclear receptors, including glucocorticoid and retinoic acid receptors (24,71). Furthermore, a subsequent search using the Ensembl mouse regulatory build (version 4) revealed ERR␤ binding to the proximal Dusp1 promoter in embryonic stem cells within the same region we identified (8,19).…”
Section: Discussionsupporting
confidence: 80%
“…NGF increases MKP-1 protein levels through both an active transcriptional mechanism and a decrease of protein degradation. The induction of MKP-1 mRNA by NGF was rapid (within 30 min) and completely blocked by actinomycin, consistent with data reported in other experimental systems (37,43). In fact, MKP-1 is considered an early response gene (20) whose transcriptional activity is controlled via a strong block of elongation in the exon I of the gene (44).…”
Section: Ngf Induces Mitochondrial Localization Of Mkp-1 Protein-supporting
confidence: 75%
“…GM cells were maintained in minimum essential medium with 0.5% FBS for 3 days to arrest cells in G 0 /G 1 phase of the cell cycle, and the effects of phosphatases on p53-mediated arrest were assessed in the presence or absence of the phosphatase inhibitor vanadate. Of note, vanadate has recently been shown to inhibit MKP1 activity in vivo (59). As shown in Fig.…”
Section: Fig 3 Transcriptional and Translational Inhibition Of Mkp1mentioning
confidence: 81%